Anti-Trichomonas vaginalis activity of chalcone and amino-analogues - Trein, Márcia Rodrigues (2019)
Trichomoniasis is the most common non-viral sexually transmitted disease worldwide and can lead to serious consequences in reproductive health, cancer, and HIV acquisition. The current approved treatment present adverse effects and drug resistance data on this neglected parasitic infection is underestimated. Chalcones are a family of molecules that present biological applications, such as activity against many pathogenic organisms including protozoan pathogens. Chalcone (1) and three amino-analogues (2–4) were synthesized by Claisen–Schmidt condensation reaction and had their activity evaluated against the parasitic protozoan Trichomonas vaginalis. This bioassay indicated the presence and position of the amino group on ring A was crucial for anti-T. vaginalis activity. Among these, 3′-aminochalcone (3) presented the most potent effect and showed high cytotoxicity against human vaginal cells. On the other hand, 3 was not able to exhibit toxicity against Galleria mellonella larvae, as well as the hemolytic effect on human erythrocytes. Trophozoites of T. vaginalis were treated with 3, and did not present significant reactive oxygen species (ROS) accumulation, but induced a significantly higher ROS accumulation in human neutrophils after co-incubation. T. vaginalis pyruvate:ferredoxin oxidoreductase (PFOR) and β-tubulin gene expression was not affected by 3.